Service management in dynamic e-business environments - O'Connell, Marcus (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2006)
Internet technologies are facilitating the development of an environment where companies are outsourcing activities that are not a part of their core competencies to third-party service providers. Customers and service providers can locate and identify each other over the Internet, negotiate the terms and conditions electronically, connect with each other dynamically, transact business and cease their relationship when the service is no longer required. One of the key enabling factors for the provision of services in this environment is the agreement of an electronic contract between the service provider and service consumer. This contract known as a Service Level Agreement (SLA) defines the terms and the quality of the service that is to be provided and the actions to be taken should the agreed service or quality not be met. With the introduction of these contracts, a requirement has arisen for a framework to manage and enable the service provider to meet the guarantees that are defined in each SLA contract.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin